1996
DOI: 10.1016/s1010-7940(96)80297-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of various designs of 19 mm pericardial aortic valve bioprosthesis

Abstract: The hemodynamics of five designs of 19 mm pericardial aortic valve bioprostheses were examined in 47 resting patients by Doppler echocardiography. The salient differences among the five designs are that valve leaflets are mounted inside the support frame in one (the Carpentier-Edwards valve, evaluated in 4 patients) and outside the frame in the other four (the Ionescu-Shiley (16 patients), Mitroflow (4), Bioflo (8) and Labcor-Santiago (15)); and that two models have either total (Bioflo) or partial (Labcor-San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Intuitively, surgeons avoid inserting 19-or 21-mm bioprostheses in patients with a body surface area above 1.7 m 2 . 2,9,10 The alternatives to implanting a small bioprosthesis include mechanical valve replacement, patch enlargement of the aortic anulus, 3 or implantation of a stentless bioprosthesis. 15,19 Mechanical valves have a proportionally larger effective orifice area for a given anulus size and have been shown to produce lower gradients when compared with similarly sized bioprostheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intuitively, surgeons avoid inserting 19-or 21-mm bioprostheses in patients with a body surface area above 1.7 m 2 . 2,9,10 The alternatives to implanting a small bioprosthesis include mechanical valve replacement, patch enlargement of the aortic anulus, 3 or implantation of a stentless bioprosthesis. 15,19 Mechanical valves have a proportionally larger effective orifice area for a given anulus size and have been shown to produce lower gradients when compared with similarly sized bioprostheses.…”
Section: Discussionmentioning
confidence: 99%
“…15,19 Mechanical valves have a proportionally larger effective orifice area for a given anulus size and have been shown to produce lower gradients when compared with similarly sized bioprostheses. 8,10 However, elderly patients are at increased risk for anticoagulant-related hemorrhage; therefore mechanical valve replacement may be inadvisable. Sommers and David 3 demonstrated that anulus-enlarging procedures resulted in long-term survivals comparable with those of patients receiving larger aortic prostheses; however, the operative mortality of aortic valve replacement increased from 3.5% to 7.1% when enlargement of the aortic anulus was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation